Development of interactive-based civic education encyclopedia learning media to improve Pancasila student profiles - Nadya Putri Saylendra; Erwin Susanto; MSW Sona Minasya; Fani Kardina; Karna Januar (Jurnal Civics: Media Kajian Kewarganegaraan)
The Pancasila Student Profile must be implemented in students to cultivate their capacity, accomplishments, and virtuous demeanor. The objective of this project is to create an interactive multimedia encyclopedia learning tool for Pancasila and citizenship education, with the purpose of enhancing the knowledge and understanding of Pancasila among students at Korpri Karawang High School. The study methodology employed is a research and development technique utilizing the ADDIE paradigm, incorporating a mixed method approach. Methods for gathering data using a questionnaire. The employed data analysis techniques include deductive analysis, inductive analysis, reliability testing, validity testing, normalcy testing, homogeneity testing, independent samples mean testing, and hypothesis testing. The findings indicated that the evaluation of the civic education Encyclopedia learning media validation tool demonstrated its suitability at a rate of 80%. After being provided with civic education encyclopedia learning material, there has been a notable disparity in the enhancement of the Pancasila students' profile among the class X students at Korpri Karawang High School. The comparative sample test conducted on the experimental class using the paired sample test yielded a significance result of 0.000. This indicates that the null hypothesis H0: μc = μk is rejected, as 0.000 is less than 0.05. Consequently, the alternative hypothesis H1: μc μk is accepted. The research suggests that teachers should include technology into the learning process by utilizing civic education encyclopedia learning media products. These products may be effectively utilized to enhance student learning.